Systematic literature review: Curriculum development principle - Amanda Azalia; Deswa Putri Lerian; Erwin Taufik; Sarah Nurul Izzah; Surya Nugraha; Ghaitsa Zahira Arya (Universitas Pendidikan Indonesia, 2023)
Curriculum development is significant to do. The curriculum is the core of the essential educational process carried out in various schools. Indonesia has undergone several changes to the newest curriculum, namely the independent curriculum. Changes in the education curriculum must adapt to the times without leaving the relevant cultural values of society. The method used in this study is a literature study through sources related to the principles of curriculum development. Curriculum development sources include; empirical data, experimental data, folklore, and general community knowledge. The directions in curriculum development are divided into two things: (1) General Principles, which include; the principle of relevance, the principle of flexibility, the principle of continuity, the principle of practicality, and the principle of effectiveness, (2) Specific Principles include; principles of determining educational goals, selecting educational content, selecting teaching and learning processes, selecting media and teaching tools, and principles relating to assessment. The curriculum plays a vital role in determining the success of education because the existence of the curriculum is concrete evidence in trying to achieve national education goals. Abstrak Kurikulum menjadi inti dari proses pendidikan yang penting dilakukan di berbagai sekolah. Indonesia telah mengalami beberapa kali pergantian sampai kurikulum terbaru, yaitu kurikulum merdeka. Perubahan kurikulum pendidikan haruslah menyesuaikan dengan perkembangan zaman tanpa meninggalkan nilai-nilai budaya masyarakat yang relevan. Metode yang digunakan pada penelitian ini adalah studi kepustakaan melalui sumber yang berkaitan dengan prinsip pengembangan kurikulum. Sumber-sumber pengembangan kurikulum, meliputi; data empiris, data eksperimen, cerita rakyat dan pengetahuan umum masyarakat. Adapun prinsip-prinsip dalam pengembangan kurikulum terbagi atas dua hal: Prinsip Umum, yang meliputi; prinsip relevansi, prinsip fleksibilitas, prinsip kontinuitas, prinsip praktis, dan prinsip efektivitas, Prinsip Khusus, yang meliputi; prinsip penentuan tujuan pendidikan, prinsip pemilihan isi pendidikan, prinsip pemilihan proses belajar mengajar, prinsip pemilihan media dan alat pengajaran, dan prinsip yang berkenaan dengan penilaian. Kurikulum berperan penting dalam menentukan keberhasilan pendidikan, karena keberadaan kurikulum menjadi salah satu bukti nyata dalam tercapainya tujuan pendidikan nasional. Kata Kunci: Kurikulum; pengembangan kurikulum; prinsip pengembangan